ANALISIS NILAI SOSIAL BUDAYA DALAM CERITA ANAK DAN KESESUAIANNYA DENGAN TAHAP PERKEMBANGAN PESERTA DIDIK DI SEKOLAH DASAR - Anggraeni, Ria; Saepurokhman, Asep; Hidayat Sutisna, Rony (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Storybooks in elementary schools are often merely used for reading practice or simple entertainment. However, a critical issue arises when the socio-cultural values within these stories are conveyed through complex metaphors or morally ambiguous characters. For elementary school students, this risks causing misinterpretations due to their cognitive limitations. Driven by this problem, this study aims to dissect the socio-cultural values, examine their presentation, and evaluate the suitability of three stories “Si Kancil dan Seruling Ajaib”, “Gajah yang Sombong”, and “Pangeran Katak” in relation to children's psychological development stages. This study employs a descriptive qualitative method through an in-depth text analysis without involving direct testing on students. Data were analyzed by contrasting sociological aspects, such as social values and norms, against developmental theories for children aged 7–11. These theories encompass concrete operational cognitive capacity, psychosocial and emotional conditions, and moral reasoning. The findings reveal that a story's suitability heavily relies on a linear plot and a clear, real-world cause-and-effect relationship that aligns with the child's daily experiences. Conversely, stories depicting trickery disguised as cleverness tend to trigger moral confusion. Through this mapping, this research successfully formulates a critical-scientific curation pattern. This framework serves as a practical guide for both teachers and parents in selecting the right reading materials to effectively foster children's character development.